Targeting ferroptosis: novel therapeutic approaches and intervention strategies for kidney diseases - Luo, Yanfang; Long, Muyang; Wu, Xueqin; Zeng, Liuting (Frontiers in Immunology, 2025)
Chronic kidney disease (CKD), characterized by structural, functional, and metabolic derangements, remains a leading cause of end-stage renal disease (ESRD) with profound global health burdens. The kidney’s high oxygen demand for blood filtration renders it exquisitely sensitive to redox imbalance—an aberration common to both CKD and acute kidney injury (AKI) that, when coupled with iron dysregulation, unleashes ferroptosis: a non-apoptotic, iron-dependent form of regulated cell death driven by iron accumulation, lipid peroxidation, and antioxidant defense impairment (e.g., GPX4/SLC7A11 dysfunction), cascades to which the redox-sensitive kidney is uniquely predisposed. While ferroptosis has been linked to AKI, diabetic nephropathy (DN), and renal fibrosis, existing reviews largely suffer from two limitations: they either focus on single kidney disease entities (e.g., only AKI or DN) or reiterate generic ferroptosis mechanisms, lacking a unified pathophysiological framework that bridges acute insults, chronic fibrosis, and even renal carcinogenesis. Addressing this gap, this review offers three integrated contributions: first, it positions ferroptosis as a convergent metabolic executioner across a broader spectrum of kidney diseases—encompassing AKI, DN, renal interstitial fibrosis, systemic lupus erythematosus (SLE) nephritis, autosomal dominant polycystic kidney disease (ADPKD), renal cell carcinoma (RCC), and contrast-induced nephropathy (CIN)—while emphasizing cell type-specific vulnerabilities: tubular epithelial cells (susceptible via mitochondrial dysfunction), podocytes (via iron overload), and immune cells (e.g., neutrophils/macrophages in SLE nephritis) exhibit context-dependent ferroptosis regulation, governed by cell type-specific modulators [e.g., Nrf2 in tubules, heme oxygenase-1 (HO-1) in macrophages, and sirtuins in podocytes]. Second, it reconciles seemingly disparate findings through a redox-metabolic lens—e.g., dual roles of HO-1 (protective via heme degradation vs. pro-ferroptotic via iron release) or iron overload (driving injury in AKI vs. targeted therapy in RCC)—by clarifying disease-specific regulatory mechanisms: PKD1 mutation-driven mitochondrial defects in ADPKD, DPP9-Nrf2-mediated sorafenib resistance in RCC, and PPARα–FABP1 axis dysregulation in IgA nephropathy, alongside shared core pathways (e.g., GPX4/SLC7A11 as central checkpoints). Third, it integrates translational insights rarely synthesized in prior work: mapping natural compounds (icariin II and artesunate), repurposed drugs (sorafenib and melatonin), and novel modulators to disease stages (e.g., Lip-1 for fibrosis and salinomycin for RCC stem cells); highlighting strategies to reverse ferroptosis-related drug resistance (targeting DPP9 in RCC); and identifying ferroptosis-related genes (ACSL4 and PDIA4) as prognostic biomarkers. Accumulating clinical and experimental evidence confirms ferroptosis as a pivotal driver of kidney disease onset and progression. This review not only synthesizes ferroptosis pathophysiology and research advances but also delineates disease-tailored therapeutic strategies. By addressing key knowledge gaps—crosstalk between ferroptosis and other cell death modalities (e.g., pyroptosis), lack of kidney-specific clinical biomarkers, and underexplored roles in autoimmune nephritides—it provides a conceptual roadmap for mechanism-based diagnostics, precision therapeutics, and rational drug combinations, transcending traditional disease boundaries to advance clinical translation for both primary and secondary kidney diseases.